CD30 expression by bone marrow mast cells from different diagnostic variants of systemic mastocytosis. Issue 6 (20th September 2013) - Morgado, José M; Perbellini, Omar; Johnson, Ryan C; Teodósio, Cristina; Matito, Almudena; Álvarez‐Twose, Iván; Bonadonna, Patrizia; Zamò, Alberto; Jara‐Acevedo, Maria; Mayado, Andrea; Garcia‐Montero, Andrés; Mollejo, Manuela; et al.
<x xml:space="preserve">Abstract</x> Aims CD30 expression by bone marrow (BM) mast cells (MC) has been reported recently in systemic mastocytosis (SM) patients. The aim of this study was to investigate the potential diagnostic and prognostic value of CD30 expression in SM as assessed by multiparameter flow cytometry. Methods and results A total of 163 consecutive BM samples corresponding to 142 SM patients and 21 non‐mastocytosis cases were studied. CD30 was positive in most SM patients (80%), but in only one non‐mastocytosis case (4.8%). When combined with CD25, CD30 contributed to an improved accuracy over that of CD25 alone (98% versus 93%) mainly because most (eight of nine) of the well‐differentiated SM (WDSM), who lacked CD25, were CD30+. Similar levels of expression of CD30 were observed among all different subgroups of SM except mast cell leukaemia; among indolent SM (ISM) patients, no significant association was observed between the levels of CD30 expression and other clinical and biological features of the disease. Conclusions The increased expression of CD30 associated with absence of CD25 contributes to the diagnosis of WDSM and its distinction from other subtypes of SM. By contrast, CD30 expression did not contribute either to prognostic stratification of ISM or to the differential diagnosis between ISM and aggressive SM cases.